Spirometric nomograms for normal children and adolescents in Puerto Rico - MARIO CHEN-MOK; SHRIKANT I. BANGDIWALA (Instituto Nacional de Salud Pública, 1997)
Objective. The use of spirometric reference values specific to the population being tested is preferable. A study carried out in Puerto Rico is used here to develop nomograms for normal children and adolescents based on age and height, two variables that have been found to be good predictors of pulmonary function. Material and methods. The data for healthy individuals aged 5 to 18 were extracted (108 girls and 107 boys) from a larger study of spirometric measurements collected on 4 527 individuals attending medical services in Puerto Rico. Several models were tested for the prediction of FEV1, FVC and the ratio FEV1/FVC. The best models were selected for each gender, and nomograms were developed showing the fifth, twenty-fifth, fiftieth, seventy-fifth, and ninety-fifth percentile of the predicted values according to age and height separately. Results. The best models were those using the logarithm of the pulmonary function and the cube of height (R2= 0.79-0.81), and age without transformation (R2= 0.73-0.77). Corresponding nomograms were developed based on these models. The ratio showed little variation for different ages and heights. Conclusions. Pulmonary function can be efficiently predicted by age and height. Nomograms provide a simple way to use spirometric references that can be incorporated to clinical practice. Objetivo. Desarrollar nomogramas espirométricos para niños y adolescentes portorriqueños, de acuerdo con edad y estatura. Material y métodos. Se extrajeron datos de individuos sanos de edades entre 5 y 18 años (108 niñas y 107 niños) de un estudio mayor, en el cual se recolectaron medidas espirométricas en 4 527 individuos que se presentaron en los servicios médicos en Puerto Rico. Se probaron varios modelos en la predicción del volumen de espiración forzada en un segundo (FEV1), de la capacidad vital forzada (CVF) y la razón VEF1/CVF. Se seleccionaron los mejores modelos para cada sexo y se desarrollaron los nomogramas mostrando los percentiles 5, 25, 50, 75 y 95 de los valores predichos por edad y estatura separadamente. Resultados. Los mejores modelos fueron aquellos con el logaritmo de la función pulmonar y el cubo de la estatura (R2= 0.79-0.81), y edad sin transformación (R2= 0.73-0.77); con base en estos se desarrollaron los nomogramas. La razón presentó poca variación entre las diferentes edades y estaturas. Conclusiones. La función pulmonar puede ser predicha eficientemente por la edad y la estatura. Los nomogramas permiten usar fácilmente los valores espirométricos de referencia incorporándolos en la práctica clínica.